Measurement of air cooling characteristics for the several surface types of Li-Ion battery - Byelyayev, A.A.; Fedorchenko, D.V.; Khazhmuradov, M.A.; Lukhanin, O.A.; Lukhanin, O.A.; Martynov, S.O.; Rudychev, Y. V.; Sporov, E.O.; Rohatgi, U.S. (Вопросы атомной науки и техники, 2013)
The system of air cooling for Li-Ion batteries is considered. Experimental setup included thermal chamber and Li-Ion battery cell simulators with temperature sensors. We investigated static and dynamic cooling regimes for several types of cooling surfaces, for different gaps between the simulators and flow rates. Experimental results are compared to the data of computer modelling using SolidWorks Flow Simulation software. The cooling efficiencies of the various surfaces for static and transient heat emission modes are compared.